A comparison of model reduction techniques based on modal projection for structures with frequency-dependent damping. (June 2017) - Rouleau, Lucie; Deü, Jean-François; Legay, Antoine
Highlights: Reduction techniques based on modal projection are reviewed. Efficiency and accuracy of reviewed methods are compared through numerical examples. The multi-model approach offers the best compromise between accuracy and efficiency. Abstract: Frequency response functions are often used in the design of damped structures to assess the level of vibration and evaluate the performances of a damping treatment. Rather than evaluating frequency sweeps on a large-scale finite element system, the frequency response functions can be efficiently computed through model reduction techniques. This paper reviews and compares the reduction techniques based on modal projection which have been developed for structures with frequency-dependent damping, such as structures treated with constrained viscoelastic layers. The insight obtained by this comparison allows to make a motivated choice for a particular model reduction technique. All reviewed methods are quantitatively compared on two illustrative examples.